2020
DOI: 10.1371/journal.pone.0235566
|View full text |Cite
|
Sign up to set email alerts
|

Induction of fatigue-like behavior by pelvic irradiation of male mice alters cognitive behaviors and BDNF expression

Abstract: Fatigue and cognitive deficits are often co-occurring symptoms reported by patients after radiation therapy for prostate cancer. In this study, we induced fatigue-like behavior in mice using targeted pelvic irradiation to mimic the clinical treatment regimen and assess cognitive behavioral changes. We observed that pelvic irradiation produced a robust fatigue phenotype, a reduced rate of spontaneous alternation in a Y-maze test, and no behavioral change in an open field test. We found that reversal learning fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The fact that mice do not display fatigue in a tail irradiation model is expected and does not contradict previous observations ( 42 45 ), as this model was used not to explain a unifying mechanism behind radiation-induced fatigue but to demonstrate a previously unidentified skin-specific mechanism contributing to fatigue, which can be reliably measured in rats. Certainly, there are multiple mechanisms contributing to fatigue in both humans and animal models.…”
Section: Discussionsupporting
confidence: 59%
“…The fact that mice do not display fatigue in a tail irradiation model is expected and does not contradict previous observations ( 42 45 ), as this model was used not to explain a unifying mechanism behind radiation-induced fatigue but to demonstrate a previously unidentified skin-specific mechanism contributing to fatigue, which can be reliably measured in rats. Certainly, there are multiple mechanisms contributing to fatigue in both humans and animal models.…”
Section: Discussionsupporting
confidence: 59%
“…Mouse models of accelerating aging (SOD1-knockout mice) show a selective deficit in reversal learning (Logan et al, 2018), suggesting that aging may primarily cause a problem in behavioral flexibility. An interesting observation was made in reversal learning for mice in which fatigue is induced by pelvic irradiation (Wolff et al, 2020): fatigued mice showed reduced performance in the task, but not because of a learning deficit but because they engaged the task at a slower pace, illustrating the value of the PhenoTyper being able to distinguish between the two.…”
Section: Measuring Learning and Cognitive Functionsmentioning
confidence: 99%
“…In each Y maze assessment, SV and HV mice displayed normal spontaneous alternation (Fig. 4E), suggesting comparable cognitive ability regarding exploration and acute spatial memory ( 48 ). At the Late timepoint, HV animals exhibited increased mobility assessed by total Y maze arm entries, as well as total distance travelled, average speed, and immobility (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Interorgan crosstalk is inherently bidirectional (15,16) and vagal brain arcs likely shape neurological side effects linked to HCC. We next explored whether hepatic vagotomy altered behaviors associated with liver cancer (e.g., aberrant fatigue) (46)(47)(48)(49).…”
Section: Ach Signaling Affects Cd8+ T Cell Anti-tumor Activitymentioning
confidence: 99%
See 1 more Smart Citation